Optically-stimulated desorption of "hot" excimers from pre-irradiated Ar solids - Gumenchuk, G.B.; Khyzhniy, I.V.; Ponomaryov, A.N.; Bludov M.А.; Uyutnov S.А.; Belov, A.G.; Savchenko, E.V.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Electronically-induced desorption from solid Ar pre-irradiated by a low-energy electron beam was investigated by activation spectroscopy methods—photon-stimulated exoelectron emission and photon-stimulated luminescence in combination with spectrally-resolved measurements in the VUV range of the spectrum. Desorption of vibrationally excited argon molecules Ar2 *(n) from the surface of pre-irradiated solid Ar was observed for the first time. It was shown that desorption of «hot» Ar2 *(n) molecules is caused by recombination of self-trapped holes with electrons released from traps by visible-range photons. The possibility of optical stimulation of the phenomenon is evidenced.